Autoritarismo, fascismo e educação : ainda a premência de que Auschwitz não se repita - Ferreira, João Vicente Hadich (Editora Oficina Universitária, 2022)
The extreme relevance and timeliness of this book [...] becomes evident when we consider Theodor Adorno's warning about the persistence of the objective conditions that generate fascism, even within democratic societies. [...] The reader will have no difficulty in recognizing the extreme relevance of this book [...], as its reflection reflects problems that are not part of an overcome historical past, but reverberate in current Brazilian society, under the impetus of the catastrophe ethical and social represented by recent Bolsonarism. It is relevant to note that the beginning of the doctoral research that originated the present work dates from the year 2017, a time when the serpent's egg was being slowly gestated, trans- appearing in the morally pernicious mentality of the “School without Party” movement. [...] One of the great merits of the reflection presented in this book is to demystify the public repulsion for the sphere of politics, which in itself integrates the set of fascist syndrome symptoms. Contrary to the mentality of refusing politics, the author emphasizes the urgency of an authentic and autonomous politicization of the sphere of power, so that a potentially public exercise becomes possible. resistant to the spread of barbarism. [...] Hannah Arendt [...] reminds us that “politics” is the sphere of public debate between different people, moved by the perspective of a common world. True politics translates into the exercise of freedom potentially aimed at breaking the state of exception that currently silences public debate and massacres all those who represent difference. [...] The fascist [...] does not want to conserve anything, because his desire, repressed, or often declared, is aimed at the destruction of everything that is possible, from the lives of people who exist on the margins of normality. to the democratic institutions themselves. [...] In tune with the reflections of Theodor Adorno, Hannah Arendt, and other thinkers focused on the critique of fascism, [...] to understand what education is, in this work, we must move away from the very instrumental aspects present at school, seeking to understand this term as synonymous with the formation of the spirit, in the opposite sense to barbarism. [...] Readers who are in tune with a broad understanding of education, aimed at de-barbarization and pacification of society, and above all aimed at combating all types of prejudice, will know how to find in this book an intellectually stimulating, enlightening and readable work. pleasurable